Significance of Consumption Patterns and ABC/FSN Matrix to Optimize Vital Drugs Inventory Management - Nang Nwe Ni Hlaing; Cha-oncin Sooksriwong; Farsai Chanjaruporn; Oraluck Pattanaprateep (Faculty of Pharmacy, Universitas Gadjah Mada)
Drug shortage affects patient’s life, especially life-saving medicines. The main objective of the study was to analyze the retrospective consumption data from 2016 in order to optimize the inventory management of vital drugs. 136 of vital drug items were categorized by ABC (Always Better Control) and FSN (Fast, slow and non-moving) matrix and analyzed the consumption patterns of vital drugs in each group. Total consumption value for vital drugs during 2016 were 361,091,149 Thai Baht. ABC and FSN matrix were sub-categorized into Category I (AF, AS, AN, BF, CF), Category II (BS, BN CS) and Category III (CN). Irregular consumption patterns from Category I and II, required special attention regarding stock control to overcome shortage and oversupply. Although Category III consists of non-moving items, these drugs have to be in stock in sufficient amount for emergency issues. Depending on the nature of consumption patterns, different inventory control methods are necessary for different characteristics of demand patterns.